Angiosarcoma of the breast with hypofibrinogenemia: A rare case report and review of the literature - An, Ran; Ma, Jing-Yi; Ni, Xi-Hao; Wang, Chang-Liang (Frontiers in Oncology, 2022)
Background: Breast angiosarcoma is a rare malignant  tumor, accounting for approximately 0.04% of all breast malignancies. Angiosarcoma of the breast with hypofibrinogenemia is even rarer and has not been described in man. Breast angiosarcoma is associated with high metastatic potential and poor prognosis, and there is no specific manifestation in imaging. At present, surgery is considered to be the only effective treatment. There is no unified standard for postoperative adjuvant radiotherapy and chemotherapy. Case Presentation: A 30-year-old female patient underwent left breast mass resection under local anesthesia on May 22, 2014. Postoperative pathology showed a vasogenic tumor. On November 10, 2017, she visited us again due to left breast swelling and pain during lactation, and underwent breast mass puncture. She was diagnosed with breast hematoma and fibrinogen reduction. On November 14, 2017, mastectomy was performed under tracheal intubation and general anesthesia, and the fibrinogen gradually returned to normal after surgery. Pathological examination showed a hemangiosarcoma with hematoma formation in the left breast. According to the pathological findings and after comprehensive evaluation, the patient underwent modified radical mastectomy for left breast cancer and right axillary sentinel lymph node biopsy on December 5, 2017. The patient died on January 28, 2018 due to rupture and hemorrhage of liver cancer and hemorrhagic shock. Conclusion: Breast angiosarcoma with hypofibrinogenemia is a rare and highly aggressive malignancy. Clinicians should be familiar with its clinicopathological features and diagnostic criteria. Multidisciplinary approach is recommended to benefit the patients.